Design of micro–mesoporous zeolite catalysts for alkylation. Issue 56 (24th May 2016) - Fu, Xiaoqin; Sheng, Xiaoli; Zhou, Yuming; Fu, Zhiwei; Zhao, Shuo; Bu, Xiaohai; Zhang, Chao
Abstract : The hierarchically micro–mesoporous zeolite Y provides preserved shape selectivity in combination with shorter diffusion pathways via the mesopores, leading to superior catalyst effectiveness. Abstract : Hierarchical zeolite Y was hydrothermally synthesized using ionic liquid 1-methyl-3-[3′-(trimethoxysilyl)propyl]imidazolium chloride, which was added into the conventional synthesis composition for crystalline microporous aluminosilicate as a mesopore-directing agent. An extremely short diffusion path length and abundant exposed acid sites in the hierarchical zeolite Y made it suitable for the catalytic transformation of bulky molecules. Then the catalytic performance of hierarchical zeolites Y was investigated using the alkylation of o -xylene with styrene. The ionic liquid directed hierarchical zeolite Y exhibited a remarkably high catalytic activity and long catalytic lifetime for the production of 1-phenyl-1-xylylethane via alkylation reaction, as compared with that of solely microporous zeolite Y. The distinct catalytic performances of the novel hierarchical zeolite Y could be attributed to the enhancement of medium strong acid amount and its micro–mesoporous structural properties which are favorable for the fast diffusion of products.